Corncob-supported Ag NPs@ ZIF-8 nanohybrids as multifunction biosorbents for wastewater remediation: Robust adsorption, catalysis and antibacterial activity. (10th November 2020) - Meng, Xin; Duan, Chao; Zhang, Yanling; Lu, Wanli; Wang, Wenliang; Ni, Yonghao
Abstract: Comprehensive utilization of bio-based polymers, such as cellulosic materials, for water purification has drawn intensive attention in recent years. Herein, we demonstrate using cellulose-rich corncob residues as scaffolds for in-situ anchoring Ag NPs decorated ZIF-8 nanohybrids, to fabricate multifunction biosorbents with robust adsorption-catalytic performance and antibacterial activity for the above purpose via a simple 'tea bag' strategy. Results show that upon delignification and TEMPO oxidation, the porous corncob particles have high contents of cellulose fraction and carboxyl groups, with rough surfaces, thus facilitating the anchoring and dispersion of the nanosized ZIF-8s via enhanced coordination. The corncob-supported porous ZIF-8s, loaded with well-dispersed Ag NPs in their matrix, can lead to corncob-based adsorbents (Ag NPs@ ZIF-8s/P-OCBs) with excellent adsorption, catalysis and antibacterial activities. The Ag NPs@ ZIF-8s/P-OCBs biosorbents have very high adsorption capacity, and the catalytic reduction for RhB and MB dyes reach 100% within 10 min, with excellent recyclability. Furthermore, the Ag NPs@ ZIF-8s/P-OCBs exhibit robust inhibition against E. coli and S. aureus (100% of GIB). The green and sustainable strategy developed can broaden the utilization of cellulose-rich agro-wastes for complex wastewater remedies. Graphical abstract: Image 1 Highlights: Corncob-based scaffolds for anchoring Ag NPs@ ZIF-8s nanohybrids as functionalized biosorbents. The biosorbents show robust adsorption, catalysis and bacterial inactivation. The corncob-supported porous ZIF-8s and well-dispersed Ag NPs contribute to the enhanced properties. The as-prepared Ag NPs@ZIF-8s/P-OCBs bio-based composites show excellent dyes removal and reusability.